2010
DOI: 10.3322/caac.20082
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Breast Cancer: The Disease, the Biology, the Treatment

Abstract: Inflammatory breast cancer (IBC) is a rare and aggressive form of invasive breast cancer accounting for 2.5% of all breast cancer cases. It is characterized by rapid progression, local and distant metastases, younger age of onset, and lower overall survival compared with other breast cancers. Historically, IBC is a lethal disease with less than a 5% survival rate beyond 5 years when treated with surgery or radiation therapy. Because of its rarity, IBC is often misdiagnosed as mastitis or generalized dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
297
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 320 publications
(313 citation statements)
references
References 140 publications
(187 reference statements)
7
297
2
7
Order By: Relevance
“…Lesions were mammographically undetectable in 6 of 25 females, possibly because of an overlying dense mammary gland pattern observed in most females. With mammography, two patients in our study showed nipple retraction, and one showed skin thickening in the mammary areola, which is more commonly observed in inflammatory breast carcinoma or invasive carcinoma [7][8][9]. The ultrasound manifestations of non-puerperal mastitis varied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lesions were mammographically undetectable in 6 of 25 females, possibly because of an overlying dense mammary gland pattern observed in most females. With mammography, two patients in our study showed nipple retraction, and one showed skin thickening in the mammary areola, which is more commonly observed in inflammatory breast carcinoma or invasive carcinoma [7][8][9]. The ultrasound manifestations of non-puerperal mastitis varied.…”
Section: Discussionmentioning
confidence: 99%
“…This type of breast cancer is usually poorly differentiated in histology from infiltrating ductal carcinoma, which often has distant metastases at the time of diagnosis [8,26]. These aforementioned manifestations in non-puerperal mastitis are slight or rare [8]. Inflammatory breast cancer usually affects females of approximately 50 years old [26,27], but non-puerperal mastitis is more common in females under 40 [5,10,11,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] This poor prognosis can be attributed to a number of factors, including the propensity for misdiagnosis of the disease due to its unique clinical presentation. [5][6][7] In contrast to most breast cancers, IBC is characterized by the lack of discernible primary tumor formation and the accumulation of cancerous epithelial cells in the dermal lymphatic vessels. 8 This lodging of IBC cells in the dermal lymphatics manifests as what appears to be inflammation, oftentimes causing clinicians to incorrectly diagnose the malady.…”
mentioning
confidence: 99%